Bio-Rational Management of Armyworm (Mythimna separata) (Lepidoptera: Noctuidae) in Chitwan Condition of Nepal - Sharma, S.; Bhandari, G. S.; Neupane, S.; Pathak, A.; Tiwari, S. (Journal of the Institute of Agriculture and Animal Science, 2018)
The armyworm, Mythimna separata Walker is the potential insect pest of maize, causes a severe damage on the vegetative and reproductive stages of that plant. Insecticides are the common practices to manage the broad categories of the pest in a maize field. Further, these practices have been linked to farmers health, biodiversity loss and declining of predatory arthropods. However, pest management by adopting a tool of integrated pest management is one potential option to reduce the pesticide in maize fields. Field experiments were conducted in winter maize with the aim of evaluating the potential bio-rational pesticides to manage the armyworm. The studies were conducted for two consecutive years in 2015/16 and 2016/17 at Rampur, Chitwan. Treatments were: Metarrhizium anisopliae (0.2ml/lit water), Nuclear Polyhedrosis Virus (NPV) ( 2.5gm/lit water), Spinosad 45% SC (0.25ml/liter of water), Multineem (Azadriachta indica) (2 .0 ml/ liter water), Furadan 3G (3-4g/ Whorl application), Lara (Chloropyriphos 50 EC + Cypermethrin 5 EC) (1.0 ml/liter of water), Magik (Imidacloprid 17.8% (0.5ml/liter of water) and Control. The experiments were completely randomized block design with three replicates. Spinosad treated plots demonstrated the lowest damage (0.884%) followed by Magik (1.27%) which was significantly lower (P< 0.05) than other treatments in 2015/2016. However, in 2016/2017, Spinosad treated plot also showed the significantly lowest damage (1.67%) followed by Lara plots (2.67%), both of these were significantly different (P< 0.05) to Metarhizium and control plots, but similar to the other treatments, but not significantly so. Maximum yield was recorded in spinosad treated plots (9.8 t/ha and 9.12 t/ha) followed by Lara treated plots (9.17t/ha and 8.69t/ha) and were lowest in control plots (4.55 t/ha and 7.18 t/ha) for both years. Hence, Spinosad (soil actinomycete bacterium, Saccharopolyspora spinose ) has the potentiality to maximize the maize yield and also potentially to the reduce the pesticide consumption and incurred cost caused by the pesticide use. Such a safe and eco-friendly insecticide has the potential to replace the synthetic pesticide and provide the benign environment to the natural predators and service providing units of multiple ecosystem services in maize agro-ecosystem.